O psicopedagogo e os problemas de aprendizagem na infância - Souza, Renivaldo Santos de (2013)
This qualitative and bibliographical dissertation points to the importance of academic research with regard to the causes of learning problems in childhood. One seeks an analysis about learning and the psycho-pedagogical interventions which can be used to solve learning problems. It is fundamental that the stages of development of children, their cognitive, emotional state and their styles of learning be researched. The research project arose from the anxieties coming from the school context, the meetings with educators, administrators and parents concerned with the children who are not managing to learn. Toward this end, the first chapter approaches psycho-pedagogy and its work field, learning and learning problems, definitions, concept and the various approaches discussed in the school. The second chapter deals with the psycho-pedagogue and learning problems in childhood and the causes such as organic, sensorial, psycho-neurological, environmental, emotional. Other aspects also approached are the diagnosis, evaluation, language, reading and writing, numbers, slowness and stopping in the learning process. In this sense the role of the educator is fundamental for new learning and the great challenge is to establish ties with the child. The psychopedagogical action needs to be present in the child, the family, the educator and the school. The third chapter emphasizes the psycho-pedagogue and the dimensions of the learning problems in the school environment. There presents itself the need to construct a space of knowledge, of communal interaction and of solidarity where educators and family can enjoy, together with the child, communal interaction, cooperation and the exchange of knowledge and become more human.